The Relationship Between Use of Smartphone and Students Interest in Reading Book - Vina Octaviani; Nanang Martono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2021)
Smartphones have become an essential part of students daily lives. Students use smartphones for various activities. Through smartphones, students can access various service sites that provide material resources such as scientific journals, scientific articles, ebooks, and others. This article aims to explain the relationship between the use of smartphones and students interest in reading books. In this research, the book in question is an ebook. The quantitative survey method was used in this study. The target of this research is students of class XII at VHS Negeri 1 Ciamis with a sample size taken 42% of the total number of 557 students, that is 233 people. The researcher used Kendalls Tau correlation test as a data analysis method. The correlation value of 0.063 and the significance value of 0.314 in this research results indicate that there is no significant relationship between the variables. The findings of this study show that there is a positive relationship between students interest in reading books and their use of smartphones, but the relationship between the two variables is very weak and insignificant at the 0.05 level, so the relationship cannot be generalized. This means that students rarely use smartphones to access ebooks but to use them for other purposes instead